MARKETING STRATEGY OF GHARAR BUSINESS SCHEMES: Mystery Box on E-Commerce Shopee Platform - Nur Rizqi Febriandika; Nabila Putri Tsany; Tipmanee Sriplod (Islamuna: Jurnal Studi Islam, 2022)
ABSTRACT Mystery box sale and purchase have developed into a fraudulent area, the prices and goods obtained are not appropriate, so consumers feel at a loss. This study aims to determine the marketing strategy and sales mechanism of the mystery box. The research method used in this research is descriptive qualitative with the type of research used in this study being observation by examining mystery box products in Shopee. Based on the results of the analysis carried out on the Shopee application, two types of keywords were found. The first keyword is the Mystery Box and the second keyword is the "Misteri Box" both have different product categories. There are ±27,000 products entitled mystery box and ±14,678 products with the name mystery box. So, it can be concluded that most of the sellers use titles with the keyword "mystery box". Mystery box on the Shopee site can be categorized as a marketing strategy that uses marketing segmentation without differentiating the market (Undifferentiated Marketing) and targeting in the form of full market coverage/mass market targeting. ABSTRAK Jual beli mystery box berkembang menjadi sebuah lahan penipuan, harga dan barang yang didapat tidak sesuai sehingga konsumen merasa rugi. Penelitian ini bertujuan untuk mengetahui strategi marketing dan mekanisme penjualan dari mystery box. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif deskriptif melalui pendekatan observasi pada produk mystery box yang ada di Shopee. Bedasarkan dari hasil analisis yang dilakukan pada aplikasi Shopee ditemukan dua jenis kata kunci, pertama adalah “Mystery box” dan kata kunci kedua adalah “Misteri Box”. Keduanya memiliki kategori produk berbeda. Hasil penelitian menunjukkan bahwa terdapat 27.000 produk yang muncul jika menggunakan kata kunci “mystery box” dan terdapat terdapat 7.000 produk jika menggunakan kata kunci “misteri Box”. Sehingga, dapat disimpulkan jika kebanyakan dari penjual lebih banyak menggunakan judul dengan kata kunci “mystery box”. Strategi pemasaran produk mystery box di Shopee dapat dikategorikan sebagai strategi marketing yang menggunakan segmentasi pemasaran tanpa membedakan pasar (Undifferentiated Marketing) dan targeting berupa cakupan pasar penuh (full market coverage/mass market targeting).